2020
DOI: 10.1111/1541-4337.12693
|View full text |Cite
|
Sign up to set email alerts
|

Craft beer: An overview

Abstract: The purpose of the work was to provide an overview on craft beer. Details and issues concerning history and legal definition market, fiscal policy, innovation, safety, healthiness, consumer profile, and sustainability are supplied. The term “craft brewery” generally refers to a brewery able to produce low volumes of beer, often made with traditional ingredients—for emulating historic styles—but also with the addition of nontraditional ingredients as a distinctiveness sign of the master brewer. In many countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 123 publications
(143 reference statements)
1
58
0
1
Order By: Relevance
“…The selection of biological resources used as inputs in beer production is an important process to achieve a desired segmentation and diversification in the competitive market of craft beer [133]. This review paper encompasses the potential exploitation of biodiversity belonging to the main classes of raw beer materials (i.e., grains and malted cereals, hops, microbes, and adjuncts), with a specific emphasis on autochthonous resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of biological resources used as inputs in beer production is an important process to achieve a desired segmentation and diversification in the competitive market of craft beer [133]. This review paper encompasses the potential exploitation of biodiversity belonging to the main classes of raw beer materials (i.e., grains and malted cereals, hops, microbes, and adjuncts), with a specific emphasis on autochthonous resources.…”
Section: Discussionmentioning
confidence: 99%
“…This work proposed a detailed dissertation about the innovative paths already explored and documented in the scientific literature. Each ingredient has peculiar characteristics [133,142], and thus, benefits and limitations affecting its concrete applications and scale-up to brewery points. From the field to the stein-there are different weaknesses and strengths affecting future development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are presented within these categories. Additionally, several reviews were found which encompassed broader overviews of the selected topics and sometimes covered several themes at once [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]; thus, their findings are presented where appropriate. Along with the key findings of the papers, we also examined the definition of low- and no-alcohol products and the funding sources for the research (see Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the reviews refer to regulations when defining beer products; for example, EU regulations require 0.5% alcohol by volume (ABV) or less for non-alcoholic beer and 1.2% ABV or less for low-alcohol beer, but they acknowledge that these regulations differ by country. Other directions of research are related to low alcoholic or alcohol-free beers within the niche of craft beer [ 13 ] and dry hopping as a technique to produce non-alcoholic beer [ 14 ].…”
Section: Resultsmentioning
confidence: 99%